Analisis Pengelolaan Penggajian Pegawai: Studi Kasus Pada Dinas Sosial Kabupaten Labuhanbatu Utara - Fadhila, Eka; Zainarti, Zainarti (STAI Darul Kamal NW Kembang Kerang, 2025)
The payroll procedure at the Social Services Office of Labuhanbatu Utara Regency is a crucial element in financial management, requiring proper management to ensure accuracy, transparency, and compliance with applicable regulations. This process includes various stages, starting from attendance data verification, basic salary calculation, allowances, to mandatory deductions. The complexity of the payroll procedures in this office is influenced by strict regulations that must be followed, including Government Regulations on Regional Financial Management. Proper payroll management impacts employee welfare, work motivation, and their productivity. This study aims to analyze the payroll procedures to identify strengths and weaknesses and provide improvement recommendations. Qualitative and case study approaches were used, involving interviews, observations, and document analysis to understand the payroll process in the office. The research results show that although the payroll procedures comply with the applicable regulations, there are still some technical and administrative obstacles that need to be addressed to improve efficiency and transparency. The use of technology-based information systems and training for relevant personnel can help address these challenges and increase employee trust in payroll management. Therefore, this research is highly relevant in supporting the creation of an accountable, transparent, and efficient payroll system in the government environment.